2016
DOI: 10.1128/msphere.00062-16
|View full text |Cite
|
Sign up to set email alerts
|

Similarly Lethal Strains of Extraintestinal Pathogenic Escherichia coli Trigger Markedly Diverse Host Responses in a Zebrafish Model of Sepsis

Abstract: Sepsis is a life-threatening systemic inflammatory condition that is initiated by the presence of microorganisms in the bloodstream. In the United States, sepsis due to ExPEC and other pathogens kills well over a quarter of a million people each year and is associated with tremendous health care costs. A high degree of heterogeneity in the signs and symptomology of sepsis makes this disease notoriously difficult to effectively diagnose and manage. Here, using a zebrafish model of sepsis, we find that similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 106 publications
(109 reference statements)
2
18
0
Order By: Relevance
“…The results revealed that out of 25 E. coli isolates, 10 isolates were oehemolytic, 2 isolates were ß-hemolytic, and 13 isolates were gamma hemolytic representing 40%, 8%, and 52% respectively. Our results agree with those reported elsewhere [16,17] where they found a large proportion of human extraintestinal E. coli isolates produce hemolysin representing (35-50%) and (35-60%) respectively, relative to normal fecal isolates (10%). Also they mentioned that epidemiological evidence indicates a role for alpha-hemolysin in extraintestinal human infections.…”
Section: Identification Of E Coli Isolatessupporting
confidence: 93%
“…The results revealed that out of 25 E. coli isolates, 10 isolates were oehemolytic, 2 isolates were ß-hemolytic, and 13 isolates were gamma hemolytic representing 40%, 8%, and 52% respectively. Our results agree with those reported elsewhere [16,17] where they found a large proportion of human extraintestinal E. coli isolates produce hemolysin representing (35-50%) and (35-60%) respectively, relative to normal fecal isolates (10%). Also they mentioned that epidemiological evidence indicates a role for alpha-hemolysin in extraintestinal human infections.…”
Section: Identification Of E Coli Isolatessupporting
confidence: 93%
“…We injected approximately 2,500 colony-forming units (CFU) of trimethoprim-resistant E . coli into the pericardial cavity of zebrafish embryos [ 75 , 78 ], incubated for 3 hours, then treated with either the original drug combination (trimethoprim + sulfamethizole) or our rationally designed combination (floxuridine + AZT). We analyzed bacterial burden at 24 hours postinoculation (hpi) at dosages analogous to human dosage (see Materials and methods and Table 4 ) [ 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…coli blood isolates #1–8 (referred to as BEC1, BEC2, etc.) are described in Barber et al [ 78 ]. Urinary tract infection (UTI) isolates and K .…”
Section: Methodsmentioning
confidence: 99%
“…Infection assay: 1.5 and 3 OD of lab strain E. coli DH5 alpha-RFP were prepared as previously described 30 and injected in the yolk of 2 dpf zebrafish. Each larva was kept separately in a 96 well plate and survival assessed through 7 dpf.…”
Section: Methodsmentioning
confidence: 99%